Anode active material, anode including the same, secondary battery including the same, and method for producing anode active material
Patent Information
- Application Number
- JP2024544990
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-13
- Filing Date
- 2023-09-11
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-09-11
AI Technical Summary
【0014】
本発明の一実施態様による負極活物質は、SiOx(0
Smart Images

Figure 2025504958000001 
Figure 2025504958000002 
Figure 2025504958000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material, a negative electrode including the same, a secondary battery including the same, and a method for producing the negative electrode active material.
[0002] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0131448, filed with the Korean Intellectual Property Office on October 13, 2022, the entire contents of which are incorporated herein by reference. [Background technology]
[0003] Recently, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have a relatively high capacity is rapidly increasing. In particular, lithium secondary batteries are in the spotlight as a driving power source for portable devices because of their light weight and high energy density. As a result, research and development efforts to improve the performance of lithium secondary batteries are being actively carried out.
[0004] In general, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, and an organic solvent. In addition, the positive electrode and the negative electrode may have active material layers formed on current collectors, each of which includes a positive electrode active material and a negative electrode active material. In general, the positive electrode uses a lithium-containing metal oxide such as LiCoO2 or LiMn2O4 as a positive electrode active material, and the negative electrode uses a lithium-free carbon-based active material or a silicon-based active material as a negative electrode active material.
[0005] Silicon-based negative active materials have been attracting attention because they have higher capacity and excellent high-speed charging characteristics compared to carbon-based active materials. However, silicon-based active materials have a disadvantage in that they have a large degree of volume expansion / contraction during charging / discharging, resulting in a large irreversible capacity and low initial efficiency.
[0006] On the one hand, in the case of silicon-based active materials, specifically silicon-based oxides represented by SiOx (0 < x < 2), there is an advantage in that the degree of volume expansion / contraction due to charge / discharge is lower compared to other silicon-based active materials such as silicon (Si). However, there is still a disadvantage that the initial efficiency of silicon-based oxides decreases due to the presence of irreversible capacity.
[0007] Regarding this, research has been continuously conducted to reduce the irreversible capacity and improve the initial efficiency by doping or inserting metals such as Li, Al, and Mg into silicon-based oxides. However, in the case of a negative electrode slurry containing a metal-doped silicon-based oxide as a negative electrode active material, there is a problem that the metal oxide formed by doping reacts with moisture to increase the pH of the negative electrode slurry and change the viscosity, thereby deteriorating the state of the manufactured negative electrode and reducing the charge / discharge efficiency of the negative electrode.
[0008] Therefore, there is a need to develop a negative electrode active material that can improve the phase stability of a negative electrode slurry containing a silicon-based oxide and improve the charge / discharge efficiency of the negative electrode manufactured therefrom.
Prior Art Documents
Patent Documents
[0009]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0010] The present invention relates to a negative electrode active material, a negative electrode containing the same, a secondary battery containing the same, and a method for manufacturing the negative electrode active material.
Means for Solving the Problems
[0011] One embodiment of the present invention is SiO xSilicon-based particles containing (0 < x < 2) and a Li compound; a carbon layer provided on at least a part of the surface of the silicon-based particles; LiF; and CF a Provided is a negative electrode active material containing (0 < a < 4).
[0012] One embodiment of the present invention provides a negative electrode containing the negative electrode active material. One embodiment of the present invention provides a secondary battery containing the negative electrode.
[0013] One embodiment of the present invention is SiO x Forming silicon-based particles containing (0 < x < 2) and a Li compound and having a carbon layer provided on at least a part of the surface; and subjecting the silicon-based particles to fluorine plasma treatment; A method for manufacturing the negative electrode active material is provided.
Effect of the Invention
[0014] The negative electrode active material according to one embodiment of the present invention is SiO x Silicon-based particles containing (0 < x < 2) and a Li compound; a carbon layer provided on at least a part of the surface of the silicon-based particles; LiF; and CF a Containing (0 < a < 4), when using the negative electrode active material, it has the effect of significantly improving the water-based processability of the slurry. Specifically, LiF is not easily soluble in water and can efficiently passivate silicon-based particles in an aqueous slurry, and acts as an artificial SEI layer during battery operation, improving the life performance of the battery. a (0 < a < 4) can increase the hydrophobicity of the carbon layer, suppress the reaction between moisture and the negative electrode active material in the aqueous slurry, and effectively passivate the particles.
[0015] Therefore, the negative electrode containing the negative electrode active material according to one embodiment of the present invention and the secondary battery containing the negative electrode have the effect of improving the discharge capacity, initial efficiency, resistance performance, and / or life characteristics of the battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] This specification will be explained in more detail below. In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0017] In this specification, when a member is said to be located "on" another member, this includes not only the case where the member is in contact with the other member, but also the case where another member is present between the two members.
[0018] The terms and words used in this specification should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0019] As used herein, the singular expression of a term includes the plural expression unless the context clearly indicates otherwise.
[0020] In the present specification, the crystallinity of the structure contained in the negative electrode active material may be confirmed by X-ray diffraction analysis. The X-ray diffraction analysis may be performed using an X-ray diffraction (XRD) analysis device (product name: D4-Endeavor, manufacturer: Bruker), or other devices used in the art may be appropriately adopted.
[0021] In this specification, the presence or absence of an element in the negative active material and the content of the element may be confirmed by ICP analysis, and the ICP analysis may be performed using an inductively coupled plasma optical emission spectrometry (ICPAES, Perkin-Elmer 7300).
[0022] In this specification, the average particle size (D 50) can be defined as the particle size at the 50% cumulative volume basis in the particle size distribution curve (graph curve of the particle size distribution diagram). The average particle size (D 50 ) can be measured, for example, using the laser diffraction method. The laser diffraction method can generally measure particle sizes in the range from the submicron region to about several millimeters, and can obtain highly reproducible and highly resolved results.
[0023] Hereinafter, preferred embodiments of the present invention will be described in detail. However, the embodiments of the present invention may be deformed into various forms, and the scope of the present invention is not limited to the embodiments described below.
[0024] <Negative electrode active material> One embodiment of the present invention is a silicon-based particle containing SiO x (0 < x < 2) and a Li compound; a carbon layer provided on at least a part of the surface of the silicon-based particle; LiF; and CF a (0 < a < 4), which provides a negative electrode active material.
[0025] The negative electrode active material according to one embodiment of the present invention contains silicon-based particles. The silicon-based particles contain SiO x (0 < x < 2) and a Li compound.
[0026] The SiO x (0 < x < 2) may correspond to a matrix in the silicon-based particle. The SiO x (0 < x < 2) may be in a form containing Si and / or SiO2, and the Si may form a phase. For example, the SiO x (0 < x < 2) may be a composite containing amorphous SiO2 and Si crystals. That is, the x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based particle contains the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved. Specifically, the SiOx (0 < x < 2) may be SiO in terms of the structural stability of the active material. x It may be a compound represented by (0.5 ≤ x ≤ 1.5).
[0027] The Li compound can correspond to a matrix within the silicon-based composite particles. The Li compound can exist in at least one form of lithium atoms, lithium silicate, silicide, and lithium oxide within the silicon-based particles. When the silicon-based particles contain the Li compound, it has the effect of improving the initial efficiency.
[0028] The Li compound can be distributed on the surface and / or inside of the silicon-based particles in a form doped into the silicon-based particles. The Li compound is distributed on the surface and / or inside of the silicon-based particles, can control the volume expansion / contraction of the silicon-based particles to an appropriate level, and can play a role in preventing damage to the active material. Also, the Li compound can be contained in terms of reducing the ratio of the irreversible phase (e.g., SiO2) of the silicon-based oxide particles and increasing the efficiency of the active material.
[0029] In one embodiment of the present invention, the Li compound may exist in the form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5) and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-based particles, and the amorphous lithium silicate may have a complex structure of the form Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.
[0030] In one embodiment of the present invention, Li may be included in an amount of 0.1 to 40 parts by weight or 0.1 to 25 parts by weight based on a total of 100 parts by weight of the negative electrode active material. Specifically, Li may be included in an amount of 1 to 25 parts by weight, and more specifically, Li may be included in an amount of 2 to 20 parts by weight. As the Li content increases, the initial efficiency increases but the discharge capacity decreases, so that when the Li content is within the above range, appropriate discharge capacity and initial efficiency can be realized.
[0031] The content of the Li element can be confirmed by ICP analysis. Specifically, a certain amount (about 0.01 g) of the negative electrode active material is taken, transferred to a platinum crucible, and completely decomposed on a hot plate by adding nitric acid, hydrofluoric acid, and sulfuric acid. Then, an inductively coupled plasma emission spectrometry (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at the characteristic wavelength of the element to be analyzed, and a reference calibration curve is created. Then, the pretreated sample solution and a blank sample are introduced into the device, and the intensity of each is measured to calculate the actual intensity. The concentration of each component is calculated by comparing it with the created calibration curve, and the total sum is converted to a theoretical value, so that the element content of the manufactured negative electrode active material can be analyzed.
[0032] In one embodiment of the present invention, the silicon-based particles may include additional metal atoms. The metal atoms may be present in the silicon-based particles in at least one form of metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may include at least one selected from the group consisting of Mg, Li, Al, and Ca. This can improve the initial efficiency of the negative electrode active material.
[0033] In one embodiment of the present invention, the silicon-based particles have a carbon layer on at least a part of the surface. In this case, the carbon layer may be partially coated on at least a part of the surface, i.e., the particle surface, or may be coated on the entire particle surface. The carbon layer imparts electrical conductivity to the negative electrode active material, and the initial efficiency, life characteristics, and battery capacity characteristics of the secondary battery may be improved.
[0034] In one embodiment of the invention, the carbon layer comprises amorphous carbon. The carbon layer may further include crystalline carbon.
[0035] The crystalline carbon can further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fluorene, carbon nanotubes, and graphene.
[0036] The amorphous carbon can appropriately maintain the strength of the carbon layer and suppress the expansion of the silicon-based particles. The amorphous carbon may be a carbon-based material formed by using at least one carbide or hydrocarbon selected from the group consisting of tar, pitch, and other organic substances as a source of a chemical vapor deposition method.
[0037] The carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose, or ketohexose, and combinations thereof.
[0038] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may include methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, or hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may include benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, or phenanthrene, etc.
[0039] In one embodiment of the present invention, the carbon layer may be an amorphous carbon layer. In one embodiment of the present invention, the carbon layer may be included in an amount of 0.1 to 50 parts by weight, 0.1 to 30 parts by weight, or 0.1 to 20 parts by weight based on 100 parts by weight in total of the negative electrode active material. More specifically, it may be included in an amount of 0.5 to 15 parts by weight, 1 to 10 parts by weight, or 1 to 5 parts by weight. When the above range is satisfied, it is possible to prevent a decrease in the capacity and efficiency of the negative electrode active material.
[0040] In one embodiment of the present invention, the thickness of the carbon layer may be 1 nm to 500 nm, and specifically, it may be 5 nm to 300 nm. When the above range is satisfied, the conductivity of the negative electrode active material is improved, the volume change of the negative electrode active material is easily suppressed, the side reaction between the electrolyte and the negative electrode active material is suppressed, and the initial efficiency and / or life of the battery are improved.
[0041] Specifically, the carbon layer can be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.
[0042] In one embodiment of the present invention, the negative electrode active material may include LiF; and CF a (0 < a < 4).
[0043] Specifically, during the production of the negative electrode active material, after forming silicon-based particles provided with a carbon layer on at least a part of the surface, F can be introduced onto the surface of the particles through fluorine plasma treatment. In this process, F can be introduced into the lithium by-products generated when doping the silicon-based particles with Li to form LiF, and F can be introduced into the carbon of the carbon layer provided on the surface of the silicon-based particles to form CF a It may exist in the form of (0 < a < 4).
[0044] The LiF formed as described above is not easily soluble in water, can efficiently passivate the silicon-based particles with an aqueous slurry, prevent the elution of the Li compound contained in the silicon-based particles, prevent the slurry from becoming basic, and has the effect of improving the aqueous processability. Also, LiF acts as an artificial SEI layer during the operation of the battery, and has the effect of improving the life performance of the battery. In one embodiment of the present invention, the LiF and CF a (0 < a < 4) may be provided on the silicon-based particles.
[0045] The LiF may be provided on the surface of the silicon-based particles, inside the carbon layer, or on the surface of the carbon layer. Specifically, the LiF may be provided on at least a part of the carbon layer, or on at least a part of the region of the surface of the silicon-based particles where the carbon layer is not provided. Without being limited thereto, the LiF may be formed at a position where lithium by-products or lithium silicate exist in the negative electrode active material. The LiF may be partially coated on the surface or may be in a form covering the entire surface. Examples of the shape of the LiF include an island type or a thin film type, but the shape of the LiF is not limited thereto
[0046] Alternatively, the LiF may be provided on the surface of the silicon-based particles by introducing F into the Li compound contained in the silicon-based particles.
[0047] The CF a (0 < a < 4) may be provided inside the carbon layer or on the surface of the carbon layer.
[0048] Specifically, the CF a (0 < a < 4) is formed by introducing F onto the surface of the carbon layer and has a structure containing a C-F bond. That is, the CF a (0 < a < 4) may be located inside the carbon layer or on the surface of the carbon layer. Specifically, it may be mainly located near the surface of the carbon layer.
[0049] By introducing F onto the surface of the carbon layer to form CF a (0 < a < 4), the hydrophobicity of the carbon layer increases, suppressing the reaction between moisture and the negative electrode active material in the aqueous slurry. Thus, the particles can be effectively passivated.
[0050] In one embodiment of the present invention, the negative electrode active material may further contain SiF b (0 < b < 4). When introducing F onto the surface of the silicon-based particles by fluorine plasma treatment, F can also be introduced into the silicon-based particles, forming a Si-F bond with silicon inside the particles and existing in the form of SiF b (0 < b < 4). The SiF b (0 < b < 4) may be located inside the silicon-based particles or on the surface of the silicon-based particles. Specifically, it may be mainly located near the surface of the silicon-based particles.
[0051] The components contained in the negative electrode active material can be confirmed by X-ray diffraction analysis (XRD) or X-ray photoelectron spectroscopy (XPS).
[0052] In the present invention, the elemental content and atomic ratio on the surface of the negative electrode active material can be confirmed by XPS (Nexsa ESCA System, Thermo Fisher Scientific (ESCA-02)). Further, the presence of LiF and CF a (0 < a < 4) can be confirmed by the XPS analysis.
[0053] Specifically, for each sample, after obtaining a survey scan spectrum and a narrow scan spectrum, a survey scan spectrum and a narrow scan spectrum can be obtained while performing a depth profile. The depth profile can be performed up to 3000 seconds using monatomic Ar ions, and the measurement and data processing conditions are as follows.
[0054] - X-ray source: Monochromated Al Kα (1486.6 eV) - X-ray spot size: 400 μm - Sputtering gun: Monatomic Ar (energy: 1000 eV, current: low, raster width: 2 mm) - Etching rate: 0.09 nm / s for Ta2O5 - Operation Mode: CAE (Constant Analyzer Energy) mode - Survey scan: pass energy 200 eV, energy step 1 eV - Narrow scan: scanned mode, pass energy 50 eV, energy step 0.1 eV - Charge compensation: flood gun off -SF:Al THERMO1 -ECF:TPP-2M -BG subtraction: Shirley
[0055] In one embodiment of the present invention, the X-ray photoelectron spectroscopy (XPS) depth profile can be measured under a monochromated Al Kα X-ray source at 0.09 nm / s for up to 3000 seconds.
[0056] In one embodiment of the present invention, when the surface of the negative electrode active material is analyzed by X-ray photoelectron spectroscopy, Li, Si, C, N, O, F, or the like is detected.
[0057] Hereinafter, the elemental content by X-ray photoelectron spectroscopy is based on 100 at% of the sum of all elements measured on a 100s basis.
[0058] In one embodiment of the present invention, the F content according to surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 10 at% or more. Specifically, the F content may be 10 at% or more and 50 at% or less, 12 at% or more and 40 at% or less, or 15 at% or more and 35 at% or less. The lower limit of the F content may be 10 at%, 12 at%, 14 at%, 15 at%, 16 at%, 18 at%, or 20 at%, and the upper limit may be 50 at%, 45 at%, 40 at%, 35 at%, 30 at%, or 25 at%.
[0059] When the F element content on the surface of the negative active material satisfies the above range, F can be sufficiently introduced into the negative active material to remove lithium by-products, and F can be effectively introduced into the carbon layer, thereby preventing the negative active material from reacting with moisture in an aqueous slurry or preventing lithium by-products from being eluted, thereby improving aqueous processability.
[0060] When the F content is equal to or greater than the lower limit of the range, the amount of F introduced into the surface of the negative active material is appropriate, and a passivation effect is exhibited. When the F content is equal to or less than the upper limit of the range, the generation of a large number of unstable F bonds such as C—F and Si-F can be prevented, and the generation of HF in the aqueous slurry and the decomposition of components such as CMC due to HF can be suppressed, thereby preventing a decrease in viscosity.
[0061] In one embodiment of the present invention, the Li content according to the surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 10 at% or more. Specifically, the Li content may be 10 at% or more and 30 at% or less, 15 at% or more and 25 at% or less, 18 at% or more and 25 at% or less, or 20 at% or more and 23 at% or less. The lower limit of the Li content may be 10 at%, 12 at%, 15 at%, 18 at%, or 20 at%, and the upper limit may be 30 at%, 28 at%, 25 at%, 24 at%, or 23 at%.
[0062] When the Li element content on the surface of the negative active material satisfies the above range, lithium silicate is uniformly formed even inside the silicon-based particles, thereby realizing appropriate capacity and efficiency. When the Li content is equal to or greater than the lower limit of the range, a sufficient amount of Li reacts with the silicon-based particles, thereby realizing appropriate efficiency. When the Li content is equal to or less than the upper limit of the range, excessive residue of Li by-products is suppressed, thereby preventing an excessive increase in the pH of the slurry and minimizing gas generation due to reaction with Si.
[0063] In one embodiment of the present invention, the Si content by surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 5 at% or less. Specifically, the Si content may be 0.1 at% or more and 5 at% or less, 1 at% or more and 5 at% or less, 2 at% or more and 4 at% or less, 2.5 at% or more and 4 at% or less, or 3 at% or more and 3.5 at% or less. The lower limit of the Si content may be 0.1 at%, 1 at%, 2 at%, 2.5 at%, or 3 at%, and the upper limit may be 5 at%, 4 at%, or 3.5 at%.
[0064] When the Si element satisfies the above content on the surface of the negative electrode active material, substances such as LiF and CF a (0 < a < 4) etc. exist in an appropriate amount, resulting in excellent passivation effect and preventing gas generation in the aqueous mixing system. During battery operation, the substances playing the role of passivation act as resistors, showing a smooth battery driving effect. When the Si content is above the lower limit of the above range, it is possible to prevent the increase in resistance associated with the excessive formation of substances playing the role of passivation. When the Si content is below the upper limit of the above range, substances playing the role of passivation can be uniformly formed to prevent gas generation problems in the aqueous process.
[0065] In one embodiment of the present invention, the C content by surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 20 at% or more. Specifically, the C content may be 20 at% or more and 70 at% or less, 30 at% or more and 60 at% or less, or 35 at% or more and 55 at% or less. The lower limit of the C content may be 20 at%, 25 at%, 30 at%, or 35 at%, and the upper limit may be 70 at%, 65 at%, 60 at%, or 55 at%.
[0066] When the C element satisfies the above content on the surface of the negative electrode active material, an appropriate amount of C-F functional groups is introduced into the carbon layer, so that the hydrophobicity of the carbon layer is increased, the reactivity with water is suppressed, and the generation of gas is also suppressed. When the C content is above the lower limit of the above range, the carbon layer is uniformly formed to minimize the exposed Si, thereby minimizing the gas generation problem. When the C content is below the upper limit of the above range, it is possible to prevent the degradation of battery performance due to excessive increase in resistance during battery operation with an appropriate amount of carbon layer.
[0067] In one embodiment of the present invention, the O content according to surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 15 at% or less. Specifically, the O content may be 2 at% to 15 at%, 2 at% to 12 at%, or 5 at% to 10 at%. The lower limit of the O content may be 2 at%, 4 at%, or 5 at%, and the upper limit may be 15 at%, 14 at%, 12 at%, or 10 at%.
[0068] When the O element on the surface of the negative active material satisfies the above content, the hydrophilicity is reduced, and the slurry gas reduction effect and the efficiency reduction due to the O functional group during battery operation can be prevented. When the O content is above the lower limit of the range, there is no excessive reduction to reduce the oxygen content, so that HF generation due to the bond of unstable F element in the aqueous process can be suppressed, and thus the decomposition reaction of materials such as CMC in the slurry can be suppressed and a sudden decrease in viscosity can be prevented. When the O content is below the upper limit of the range, the hydrophilicity is reduced and it does not easily react with water, so that gas generation can be prevented.
[0069] When the negative electrode active material of the present invention satisfies the above-mentioned element content range, F is sufficiently introduced into the negative electrode active material, lithium by-products are easily removed, and LiF is formed. F is effectively introduced into the carbon layer, and CF a The resulting LiF and CF a The amount of the aqueous solution is appropriate, and thus it is possible to prevent the negative electrode active material from reacting with water in the aqueous slurry or to prevent lithium by-products from being eluted, thereby improving the aqueous processability.
[0070] In one embodiment of the present invention, the atomic ratio of F to O (F / O ratio) in surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 1 or more and 6 or less. Specifically, it may be 1.2 or more and 5 or less, or 1.5 or more and 4.5 or less. When the above range is satisfied, F is appropriately introduced into the surface portion of the negative electrode active material, and LiF and CF aIt is easily formed, easily passivates silicon-based particles in the slurry, and when the battery is driven, LiF acts as an artificial SEI film, resulting in a remarkable improvement in the slurry processability and life performance. When it is above the lower limit of the above range, the introduction amount of F on the surface of the negative electrode active material is sufficient, which is advantageous for the passivation effect. When it is below the upper limit of the above range, a large number of unstable F bonds such as C-F and Si-F are prevented from occurring, the generation of HF in the aqueous slurry and the decomposition of components such as CMC in the slurry by HF are suppressed, and a significant viscosity decrease can be prevented.
[0071] In one embodiment of the present invention, the atomic ratio of Li to C (C / Li ratio) by surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 0.8 or more and 4 or less. Specifically, it may be 1 or more and 3.5 or less, 1.5 or more and 3 or less, or 1.7 or more and 2.5 or less. When the above range is satisfied, the contents of LiF and CF located on the surface of the negative electrode active material are appropriate, and silicon-based particles in the slurry can be easily passivated. When the battery is driven, LiF acts as an artificial SEI film, resulting in a remarkable improvement in the slurry processability and life performance. When it is above the lower limit of the above range, the carbon layer becomes uniform, the passivation effect increases and it does not react with water. When it is below the upper limit of the above range, a decrease in battery performance due to an increase in resistance during battery driving can be prevented. a The content of is appropriate, and silicon-based particles in the slurry can be easily passivated. When the battery is driven, LiF acts as an artificial SEI film, resulting in a remarkable improvement in the slurry processability and life performance. When it is above the lower limit of the above range, the carbon layer becomes uniform, the passivation effect increases and it does not react with water. When it is below the upper limit of the above range, a decrease in battery performance due to an increase in resistance during battery driving can be prevented.
[0072] In one embodiment of the present invention, the content of the LiF may be more than the content of CF a (0 < a < 4). Usually, after forming a carbon layer on the silicon-based particles, in the process of doping lithium into the silicon-based particles, the lithium by-products mainly exist on the carbon layer. Therefore, when the silicon-based particles are treated with fluorine plasma, F is preferentially introduced into the lithium by-products, so the content of LiF may be more than the content of CF a (0 < a < 4).
[0073] In one embodiment of the present invention, a lithium by-product may be present on the silicon-based particle. Specifically, the lithium by-product may be present on the surface of the silicon-based particle or on the surface of the carbon layer.
[0074] Specifically, the lithium by-product may refer to a lithium compound remaining near the surface of the silicon-based particles or the carbon layer after the silicon-based particles are manufactured. As described above, even after the acid treatment process, lithium by-products that have not reacted with the acid may remain.
[0075] The lithium by-product may include one or more selected from the group consisting of Li2O, LiOH, and Li2CO3. As in the above reaction, LiF may be formed from the lithium by-product during fluorine plasma treatment, and unreacted lithium by-product may be present on the silicon-based particles.
[0076] The presence or absence of the lithium by-product can be confirmed by X-ray diffraction analysis (XRD) or X-ray photoelectron spectroscopy (XPS).
[0077] The lithium by-product may be included in an amount of 5 parts by weight or less based on 100 parts by weight of the total negative electrode active material. Specifically, the lithium by-product may be included in an amount of 0.01 to 5 parts by weight, 0.05 to 2 parts by weight, or 0.1 to 1 part by weight. More specifically, the lithium by-product may be included in an amount of 0.1 to 0.8 parts by weight, or 0.1 to 0.5 parts by weight. When the content of the lithium by-product satisfies the above range, it is possible to reduce side reactions in the slurry and improve aqueous processability by reducing viscosity changes. When the content is below the upper limit of the above range, it is possible to prevent the slurry from becoming alkaline during formation, and to minimize the occurrence of aqueous processability issues due to side reactions or viscosity changes.
[0078] The content of the lithium by-product may be calculated by measuring the amount of the HCl solution at a specific range where the pH changes during the titration of the aqueous solution including the negative active material with the HCl solution using a titration device.
[0079] The average particle size (D 50 ) of the negative electrode active material may be 0.1 μm to 30 μm, specifically, it may be 1 μm to 20 μm, and more specifically, it may be 1 μm to 10 μm. When the above range is satisfied, the structural stability of the active material during charge and discharge can be achieved, preventing the problem that the particle size becomes excessively large and the volume expansion / shrinkage level also increases, and preventing the problem that the particle size becomes excessively small and the initial efficiency decreases.
[0080] The BET specific surface area of the negative electrode active material is 1 m 2 / g to 100 m 2 / g, specifically, it may be 1 m 2 / g to 70 m 2 / g, more specifically, it may be 1 m 2 / g to 50 m 2 / g, for example, 2 m 2 / g to 30 m 2 / g. When the above range is satisfied, during charging and discharging of the battery, the side reaction with the electrolyte can be reduced, and the life characteristics of the battery can be improved.
[0081] <Method for manufacturing negative electrode active material> One embodiment of the present invention includes the steps of forming silicon-based particles containing SiO x (0 < x < 2) and a Li compound and having a carbon layer on at least a part of the surface; and subjecting the silicon-based particles to fluorine plasma treatment; and provides a method for manufacturing the negative electrode active material.
[0082] The silicon-based particles can be formed by the steps of heating and vaporizing Si powder and SiO2 powder in a vacuum, then depositing the vaporized mixed gas to form preliminary particles; forming a carbon layer on the surface of the formed preliminary particles; and heat-treating after mixing the preliminary particles with a carbon layer formed thereon and Li powder.
[0083] Specifically, the mixed powder of the Si powder and the SiO2 powder can be heat treated at 1300°C to 1800°C, 1400°C to 1800°C, or 1400°C to 1600°C under vacuum.
[0084] The formed preliminary particles may have the morphology of SiO. The carbon layer can be formed by chemical vapor deposition (CVD) using a hydrocarbon gas or by carbonizing a material serving as a carbon source.
[0085] Specifically, the preliminary particles are put into a reactor, and then a hydrocarbon gas is subjected to chemical vapor deposition (CVD) at 600° C. to 1200° C. The hydrocarbon gas may be at least one kind of hydrocarbon gas selected from the group including methane, ethane, propane, and acetylene, and the gas may be heat-treated at 900° C. to 1000° C.
[0086] The step of heat treating the preliminary particles on which the carbon layer is formed and the Li powder after mixing them may be performed at 700° C. to 900° C. for 4 to 6 hours, specifically, at 800° C. for 5 hours.
[0087] The silicon-based particles may include the Li compound such as Li silicate, Li silicide, or Li oxide.
[0088] The particle size of the silicon-based particles can be adjusted by a method such as a ball mill, a jet mill, or air flow classification, but is not limited thereto.
[0089] As described above, at least a part of the surface of the silicon-based particle having the carbon layer is provided with a lithium compound (lithium by-product). xPreliminary particles including (0 < x < 2) are formed, and after forming a carbon layer on the preliminary particles and then doping with Li to produce the silicon-based particles, lithium compounds, i.e., lithium by-products formed by unreacted lithium, remain near the surface of the silicon-based particles.
[0090] In one embodiment of the present invention, the method for manufacturing the negative electrode active material includes a step of subjecting the silicon-based particles to fluorine plasma treatment.
[0091] The fluorine plasma treatment step includes: after placing the silicon-based particles in a plasma chamber, injecting CF4 gas; increasing the pressure inside the chamber; and forming plasma in the chamber.
[0092] The plasma treatment may be performed using RF plasma. Specifically, the pressure inside the chamber before injecting CF4 gas into the chamber may be adjusted to 0.01 torr to 0.1 torr. Preferably, the pressure may be adjusted to 0.05 torr to 0.09 torr or 0.07 torr.
[0093] Thereafter, in the step of increasing the pressure inside the chamber, the pressure inside the chamber may be adjusted to 0.1 torr to 0.5 torr. Specifically, the pressure may be adjusted to 0.15 torr to 0.3 torr or 0.2 torr.
[0094] The step of forming plasma in the chamber may be performed by applying power to the chamber. Specifically, the power may be 50 W to 300 W, 80 W to 250 W, or 100 W to 200 W.
[0095] The plasma may be held for 1 minute to 10 minutes. Preferably, it may be held for 3 minutes to 8 minutes, 5 minutes to 7 minutes, or 6 minutes.
[0096] When plasma treatment is performed satisfying the above range, F can be introduced into the silicon-based particles provided with the carbon layer in an appropriate content.
[0097] After forming plasma in the chamber and introducing F into the silicon-based particles provided with the carbon layer, the vacuum can be released at normal pressure and then the sample can be recovered.
[0098] The fluorine plasma treatment step may be repeated one or more times. Preferably, it may be repeated two or more times, and more preferably, it may be performed two or three times.
[0099] As in the present invention, when F is introduced into the negative electrode active material by a dry method using plasma, lithium inside the silicon-based particles containing the Li compound does not dissolve, and the passivation characteristics are further improved. On the other hand, when F is introduced by a method such as hydrothermal synthesis or solvothermal synthesis, the surface of the silicon-based particles becomes porous and the passivation effect is reduced.
[0100] As described above, by fluorine plasma treatment, F is introduced into the lithium by-products formed when doping lithium into the silicon-based particles to form LiF. The formed LiF easily blocks the reaction between water and the lithium compound or the silicon-based particles, and acts as an artificial SEI layer during the driving of the battery, resulting in the effect of improving the life performance.
[0101] Also, when F is introduced onto the surface of the carbon layer to form CF a (0 < a < 4), the hydrophobicity of the carbon layer increases, and the reaction between moisture and the negative electrode active material in the aqueous slurry is suppressed, so that the particles can be effectively passivated.
[0102] <Negative electrode> The negative electrode according to an embodiment of the present invention may include the above negative electrode active material. Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. Furthermore, the negative electrode active material layer may further include a binder, a thickener, and / or a conductive material.
[0103] The negative electrode active material layer may be formed by applying a negative electrode slurry including a negative electrode active material, a binder, a thickener, and / or a conductive material to at least one surface of a current collector, followed by drying and rolling. The negative electrode slurry may further include an additional negative electrode active material.
[0104] The additional negative electrode active material may be a compound capable of reversibly inserting and extracting lithium. Specific examples of the additional negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, the carbon material may be either low-crystalline carbon or high-crystalline carbon. Typical low-crystalline carbons include soft carbon and hard carbon, and typical high-crystalline carbons include amorphous, plate-like, scaly, spherical or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbons such as petroleum or coal tar pitch derived cokes.
[0105] The additional anode active material may be a carbon-based anode active material. In one embodiment of the present invention, the weight ratio of the negative electrode active material to the additional negative electrode active material contained in the negative electrode slurry may be 10:90 to 90:10, specifically, 10:90 to 50:50.
[0106] The negative electrode slurry may include a solvent for forming a negative electrode slurry. Specifically, the solvent for forming a negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.
[0107] The negative electrode slurry containing the negative electrode active material according to one embodiment of the present invention may have a pH of 7 to 11 at 25° C. When the pH of the negative electrode slurry satisfies the above range, the rheological properties of the slurry are stabilized. When the pH of the negative electrode slurry is within the above range, decomposition of carboxymethyl cellulose (CMC) used as a thickener is suppressed, a decrease in the viscosity of the slurry is prevented, and the degree of dispersion of the active material contained in the slurry can be maintained.
[0108] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but is not limited thereto.
[0109] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0110] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0111] The conductive material may be contained in an amount of 0.01% by weight to 30% by weight, and preferably 0.1% by weight to 20% by weight, based on 100% by weight of the negative electrode active material layer.
[0112] The thickener may be carboxymethyl cellulose (CMC), but is not limited thereto, and any thickener used in the art may be appropriately adopted.
[0113] In one embodiment of the present invention, the weight ratio of the negative electrode active material and the additional negative electrode active material contained in the negative electrode slurry may be 1:99 to 30:70, specifically, 5:95 to 30:70 or 10:90 to 20:80.
[0114] In an embodiment of the present invention, the total amount of the negative electrode active material contained in the negative electrode slurry may be 60 parts by weight to 99 parts by weight, specifically, 70 parts by weight to 98 parts by weight, based on 100 parts by weight of a total solid content of the negative electrode slurry.
[0115] In one embodiment of the present invention, the binder may be included in an amount of 0.5 parts by weight to 30 parts by weight, specifically 1 part by weight to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0116] In one embodiment of the present invention, the conductive material may be included in an amount of 0.5 parts by weight to 25 parts by weight, specifically 1 part by weight to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0117] In one embodiment of the present invention, the thickener may be included in an amount of 0.5 parts by weight to 25 parts by weight, specifically, 0.5 parts by weight to 20 parts by weight, more specifically, 1 part by weight to 20 parts by weight, based on 100 parts by weight of a total of solid contents of the negative electrode slurry.
[0118] The negative electrode slurry according to an embodiment of the present invention may further include a solvent for forming a negative electrode slurry. Specifically, the solvent for forming a negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.
[0119] In one embodiment of the present invention, the weight of the solid content of the negative electrode slurry may be 20 parts by weight to 75 parts by weight, specifically 30 parts by weight to 70 parts by weight, based on 100 parts by weight of the total of the negative electrode slurry.
[0120] <Secondary battery> A secondary battery according to an embodiment of the present invention may include the anode according to the embodiment described above. Specifically, the secondary battery may include an anode, a cathode, a separator interposed between the cathode and the anode, and an electrolyte, and the anode is the same as the anode described above. The anode has been described above, so a detailed description thereof will be omitted.
[0121] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0122] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase adhesion to the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0123] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be metallic lithium (Li-metal).
[0124] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0125] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and other carbon-containing substances; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one of these may be used alone or a mixture of two or more of them may be used.
[0126] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0127] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a secondary battery can be used without any particular restrictions, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture absorption ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0128] Examples of the electrolytic solution include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.
[0129] Specifically, the electrolytic solution may contain a non-aqueous organic solvent and a metal salt. Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0130] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte solution having high conductivity can be prepared, and therefore such a mixture can be used even more preferably.
[0131] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.
[0132] In addition to the components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0133] According to another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES
[0134] <Examples and Comparative Examples> Example 1 94g of powder of Si and SiO2 mixed in a 1:1 molar ratio was mixed in a reactor and then vacuum heated at 1400℃ sublimation temperature. The vaporized Si and SiO2 mixed gas was then reacted in a vacuum cooling zone with a cooling temperature of 800℃ to condense into a solid phase. The condensed particles were then crushed in a ball mill for 3 hours to produce particles with a size of 6μm. The particles were then placed in the hot zone of a CVD device while Ar gas was flowed to maintain an inert atmosphere, and methane was blown into the hot zone at 900℃ using Ar as a carrier gas, and the mixture was heated for 5 hours and 10 minutes. -1 The particles were reacted under torr to form a carbon layer on the surface of the particles, and then 6 g of Li metal powder was added and mixed with the particles with the carbon layer, followed by additional heat treatment at a temperature of 800°C in an inert atmosphere to produce silicon-based particles containing a Li compound.
[0135] 10 g of the silicon-based particles were spread thinly to a thickness of 3 mm or less and placed in an RF plasma chamber, and CF4 gas was injected under 0.07 torr to increase the pressure inside the chamber to 0.2 torr. Then, a power of 150 W was applied to the chamber to generate plasma, and the chamber was held for 6 minutes, and the vacuum was released to normal pressure, and the sample was collected. The above process was repeated two more times (total of three times) to obtain the negative electrode active material of Example 1.
[0136] Example 2 A negative electrode active material of Example 2 was obtained in the same manner as in Example 1, except that the intensity of the power applied when forming the plasma was 200 W.
[0137] Example 3 A negative electrode active material of Example 3 was obtained in the same manner as in Example 1, except that the intensity of the power applied when generating plasma was 100 W.
[0138] Comparative Example 1 A negative electrode active material of Comparative Example 1 was obtained in the same manner as in Example 1, except that the plasma treatment was not performed.
[0139] Comparative Example 2 Silicon-based particles containing a Li compound were obtained in the same manner as in Example 1, except that no plasma treatment was performed. A mixture of 0.1M Al2(SO4)3 solution and 0.1M H3PO4 solution was mixed with the silicon-based particles in a weight ratio of 5:1, and then stirred for 1 hour. The mixture was then filtered and dried to form an inorganic coating layer containing aluminum phosphate on the silicon-based particles.
[0140] Comparative Example 3 Silicon-based particles containing a Li compound were obtained in the same manner as in Example 1, except that no plasma treatment was performed. The silicon-based particles were put into a reactor, and then chemical vapor deposition (CVD) was performed using propane as a hydrocarbon gas at 700° C. for 4 hours to form an additional carbon layer on the silicon-based particles, thereby preparing a negative electrode active material.
[0141] Comparative Example 4 Silicon-based particles containing a Li compound were obtained in the same manner as in Example 1, except that no plasma treatment was performed. The silicon-based particles and 0.1M HF solution were mixed in a weight ratio of 1:7, and then stirred for 1 hour. The mixture was then filtered, dried, and heat-treated at 300° C. to produce a negative electrode active material having a LiF layer on the surface.
[0142] <Carbon layer content measurement> The content of the carbon layer was analyzed using a CS-analyzer (CS-800, Eltra).
[0143] <Measurement of Li content in negative electrode active material> The Li atom content was confirmed by ICP analysis using an inductively coupled plasma optical emission spectrometer (Perkin-Elmer 7300 ICP-OES, AVIO 500).
[0144] <Measurement of Element Content and Atomic Ratio by X-ray Photoelectron Spectroscopy (XPS)> The elemental content (at%) on the surface of the negative electrode active material was confirmed by XPS (Nexsa ESCA System, Thermo Fisher Scientific (ESCA-02)).
[0145] Specifically, for each sample, a survey scan spectrum and a narrow scan spectrum were obtained, and then a survey scan spectrum and a narrow scan spectrum were obtained while performing a depth profile. The depth profile was performed up to 3000 seconds using monatomic Ar ions. The measurement and data processing conditions are as follows.
[0146] -X-ray source: Monochromated Al Kα (1486.6 eV) -X-ray spot size: 400 μm -Sputtering gun: Monatomic Ar (energy: 1000 eV, current: low, raster width: 2 mm) -Etching rate: 0.09 nm / s for Ta2O5 -Operation Mode: CAE (Constant Analyzer Energy) mode -Survey scan: pass energy 200 eV, energy step 1 eV -Narrow scan: scanned mode, pass energy 50 eV, energy step 0.1 eV -Charge compensation: flood gun off -SF:Al THERMO1 -ECF:TPP-2M -BG subtraction: Shirley
[0147] Under the above conditions, the content of each element was calculated based on the total content of the element measured on the 100s basis (100 at%). The compositions of the negative electrode active materials produced in the above examples and comparative examples are as shown in Table 1 below.
[0148] [Table 1]
[0149] <Experimental Example 1: Discharge capacity, initial efficiency, and life (capacity retention rate) characteristic evaluation> Anode production The negative electrode material used was a mixture of the negative electrode active material produced in Example 1 and graphite (average particle size (D50): 20 μm) as a carbon-based active material in a weight ratio of 10:90. The negative electrode material, styrene-butadiene rubber (SBR) as a binder, Super C65 as a conductive material, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96:2:1:1, and the mixture was added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry.
[0150] The negative electrode slurry was applied to one surface of a copper current collector (thickness: 15 μm) at 3.6 mAh / cm 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 50 μm), which was used as the negative electrode of Example 1 (thickness of negative electrode: 65 μm). Moreover, the negative electrodes of Examples 2 and 3 and Comparative Examples 1 to 4 were produced in the same manner as in Example 1, except that the negative electrode active material of Example 1 was replaced with the negative electrode active materials of Examples 2 and 3 and Comparative Examples 1 to 4, respectively.
[0151] Secondary battery manufacturing A lithium metal foil was prepared as the positive electrode. A porous polyethylene separator was interposed between the negative and positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 4 prepared as above, and an electrolyte was injected to prepare coin-shaped half cells of Examples 1 to 3 and Comparative Examples 1 to 4, respectively.
[0152] The electrolyte used was a solution in which ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were mixed at a volume ratio of 7:3, in which 0.5% by weight of vinylene carbonate (VC) was dissolved, and LiPF6 was dissolved at a concentration of 1M.
[0153] Discharge capacity, initial efficiency, life (capacity retention rate) characteristic evaluation The secondary batteries produced in Examples 1 to 3 and Comparative Examples 1 to 4 were evaluated for discharge capacity, initial efficiency, and cycle capacity retention rate using an electrochemical charger / discharger. The cycle capacity retention rate was measured at a temperature of 25°C, with charging and discharging at 0.1C in the first and second cycles, and at 0.5C from the third cycle onwards (charge conditions: CC / CV, 5mV / 0.005 cut-off, discharge conditions: CC, 1.5V cut-off). The discharge capacity (mAh / g) and initial efficiency (%) were derived from the results of the first charge / discharge.
[0154] The capacity retention rate was calculated as follows. Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at 1st cycle)} x 100 (In the above formula, N is an integer of 1 or more.) The capacity retention rate (%) at the 50th cycle is shown in Table 2 below.
[0155] <Experimental Example 2: Processability (amount of slurry gas generated) characteristic evaluation> As the negative electrode material, a mixture of the negative electrode active material produced in the above-mentioned Examples and Comparative Examples and graphite (average particle size (D50): 20 μm) as a carbon-based active material in a weight ratio of 10:90 was used.
[0156] As the negative electrode material, styrene-butadiene rubber (SBR) as the binder, Super C65 as the conductive material, and carboxymethyl cellulose (CMC) as the thickener were mixed at a weight ratio of 96:2:1:1, and this was added to distilled water as a solvent for forming the negative electrode slurry to prepare a negative electrode slurry.
[0157] The negative electrode slurry was put into an aluminum pouch with a volume of 7 mL and sealed. The difference between the weight of the aluminum pouch containing the negative electrode slurry in the air and the weight in water at 23°C was determined, and this was divided by the density of water at 23°C to measure the volume of the gas immediately after manufacturing the negative electrode slurry.
[0158] Next, after storing the aluminum pouch containing the negative electrode slurry at 60°C for 3 days, the difference between the weight of the aluminum pouch containing the negative electrode slurry in the air and the weight in water at 60°C was determined, and this was divided by the density of water at 60°C to measure the volume of the gas after storing the negative electrode slurry for 3 days.
[0159] The difference between the volume of the gas measured after storing the negative electrode slurry for 3 days and the volume of the gas measured immediately after manufacturing the negative electrode slurry was defined as the gas generation amount and is shown in Table 2 below.
[0160]
Table 2
[0161] The negative electrode active material according to the present invention contains silicon-based particles, LiF, and CF a (0 < a < 4). In Examples 1 to 3 using the negative electrode active material of the present invention, it was confirmed that they were excellent in discharge capacity, initial efficiency, and capacity retention rate, and there was no or significantly low gas generation amount in the slurry. This is because LiF and CF contained in the negative electrode active material of the present invention aSince (0 < a < 4) passivates silicon-based particles efficiently with a slurry, and the surface of the negative electrode active material contains Li and F within the above range, it is considered that LiF is appropriately distributed on the particle surface, effectively suppressing side reactions in the slurry.
[0162] On the other hand, in Comparative Example 1, the negative electrode active material does not contain LiF and CF a (0 < a < 4), and it was confirmed that moisture in the slurry easily reacts with the silicon-based particles to generate gas, resulting in a decrease in discharge capacity, initial efficiency, and capacity retention rate.
[0163] In Comparative Examples 2 and 3, instead of the negative electrode active material containing LiF and CF a (0 < a < 4), an inorganic coating layer or an additional carbon layer is coated on the surface of the negative electrode active material. Although the amount of gas generation is slightly reduced compared to Comparative Example 1, the amount of gas generation is still large, and it was confirmed that the discharge capacity, initial efficiency, and capacity retention rate decrease.
[0164] In Comparative Example 4, LiF is coated on the surface of the negative electrode active material, and the silicon-based particles are passivated by LiF, but the degree is low, and it was confirmed that the amount of gas generation is still large and the discharge capacity, initial efficiency, and capacity retention rate are not improved.
[0165] Therefore, in the present invention, silicon-based particles, LiF, and CF a (0
Claims
1. SiO x (0<x<2) and a silicon-based particle comprising a Li compound; a carbon layer provided on at least a portion of the surface of the silicon-based particle; LiF, and CF a (0<a<4)、 A negative electrode active material comprising:
2. The surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy revealed that the F content was 10 at% or more. The negative electrode active material according to claim 1 , wherein the Li content is 10 at % or more.
3. The LiF and the CF a The negative electrode active material according to claim 1 , wherein (0<a<4) is provided on the silicon-based particles.
4. 2 . The negative electrode active material of claim 1 , wherein the F content is 10 at % or more and 50 at % or less according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy.
5. 2 . The negative electrode active material of claim 1 , wherein the Li content according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy is 10 at % or more and 30 at % or less.
6. 2. The negative electrode active material of claim 1, wherein the oxygen content of the negative electrode active material is 15 at % or less according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy.
7. 2. The negative electrode active material of claim 1, wherein a Si content of the negative electrode active material is 5 at % or less according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy.
8. 2. The negative electrode active material according to claim 1, wherein a C content according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy is 20 at % or more.
9. The negative electrode active material according to claim 1 , wherein an atomic ratio of F to O (F / O ratio) is 1 or more and 6 or less, as determined by surface analysis of the negative electrode active material using X-ray photoelectron spectroscopy.
10. The negative electrode active material according to claim 1 , wherein an atomic ratio of C to Li (C / Li ratio) according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy is 0.8 or more and 4 or less.
11. The content of LiF is a The negative electrode active material according to claim 1 , wherein the content of a is greater than (0<a<4).
12. SiF b The negative electrode active material according to claim 1 , further comprising: (0<b<4).
13. The negative electrode active material according to claim 1, comprising 0.1 to 40 parts by weight of Li based on 100 parts by weight of the total negative electrode active material.
14. The negative electrode active material of claim 1, wherein the carbon layer is included in an amount of 0.1 to 50 parts by weight based on 100 parts by weight of the total negative electrode active material.
15. SiO x forming a silicon-based particle comprising a (0<x<2) and Li compound, the particle having a carbon layer on at least a portion of the surface thereof; subjecting the silicon-based particles to a fluorine plasma treatment; The method for producing the negative electrode active material according to any one of claims 1 to 14, comprising:
16. The fluorine plasma treatment step includes: The silicon-based particles are placed in a plasma chamber and then CF 4 injecting gas; increasing the pressure within the chamber; and forming a plasma in the chamber; The method for producing a negative electrode active material according to claim 15 , comprising:
17. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 14.
18. A secondary battery comprising the negative electrode according to claim 17.
Citation Information
Patent Citations
Silicon-based lithium storage material and preparation method thereof
CN112219295A
Negative electrode active substance, negative electrode active substance material, negative electrode, lithium ion secondary battery, method for manufacturing negative electrode, method for manufacturing negative electrode active substance, and method for manufacturing lithium ion secondary battery
JP2017168466A
Negative electrode active material powder used in lithium ion secondary battery, negative electrode, and lithium ion secondary battery
JP2021057216A
Manufacturing method of negative active material, negative active material thereof and lithium secondary battery comprising the same
KR1020130045212A